2015
DOI: 10.1002/bab.1366
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sorbitol and glycerol on the stability of trypsin and difference between their stabilization effects in the various solvents

Abstract: The effect of glycerol and sorbitol on the stability of porcine pancreas trypsin was investigated in this work. Molecular dynamics simulation and thermostability results showed that trypsin has two flexible regions, and polyols (sorbitol and glycerol) stabilize the enzyme by decreasing the flexibility of these regions. Radial distribution function results exhibited that sorbitol and glycerol were excluded from the first water layer of the enzyme, therefore decrease the flexibility of the regions by preferentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…A). Although the theoretical V max was not reached here, as this value only reflects the activity without any product present, SpsADH seemed to be stabilized by sorbitol, as it has also been reported for various other proteins (Brennan et al ., ; Khajehzadeh et al ., ; Pazhang et al ., ). This allowed SpsADH to be active for an extended time period of approximately 230 h, resulting in this high yield.…”
Section: Resultsmentioning
confidence: 97%
“…A). Although the theoretical V max was not reached here, as this value only reflects the activity without any product present, SpsADH seemed to be stabilized by sorbitol, as it has also been reported for various other proteins (Brennan et al ., ; Khajehzadeh et al ., ; Pazhang et al ., ). This allowed SpsADH to be active for an extended time period of approximately 230 h, resulting in this high yield.…”
Section: Resultsmentioning
confidence: 97%
“…In many instances, a high thermostability of trypsin is usually required in some industrial and biotechnological applications. Some methods, such as immobilization, the addition of polyol and enzymatic glycation, have been used for improving the thermostability of trypsin [ 6 , 27 , 28 ]. In the present study, we improved the thermostability of trypsin by truncating the flexible region.…”
Section: Discussionmentioning
confidence: 99%
“…Cipolatti et al prepared lipase-immobilized PEGylated polyurethane particles and showed a stabilizing effect for oil ethanolysis [36]; lipase was adsorbed on the polymer, and the protection of the PEG derivative against the oil environment was effective on the enzyme. Pazhang et al showed the stabilizing effect of sorbitol and glycerol on trypsin in organic solvents [37]. As a result, immobilized enzymes were stabilized by the mechanism, wherein amphiphilic molecules are not required to bind covalently.…”
Section: Stability By Immobilizationmentioning
confidence: 99%